Mapping left-right associations: a framework using open-ended survey responses and political positions - Lukas Warode (Humanities & Social Sciences Communications)
Abstract The terms left and right are essential poles in the context of political ideology. Their meanings and understandings vary across contexts, affecting political communication, discourse, representation and polarisation dynamics. We know less about how different meanings and understandings manifest themselves beyond differential usage of the left-right scale. Building on this research gap, I measure how associations with left and right systematically vary across different political positions. I present a novel theoretical two-dimensional model distinguishing between left- and right-leaning individuals and their associations with left and right. In doing so, I propose ‘in-ideology’ (alignment with one’s political leanings) and ‘out-ideology’ (opposition to one’s leanings) as a theoretical foundation to understand diverging associations. Using data from German GLES candidate studies (2013, 2017, 2021), I introduce a methodological framework that maps left-right word associations from open-ended survey responses into a semantic space, combining these with political positions to reflect the in- and out-ideology dichotomy. The findings reveal substantive differences based on left-right positions, manifested in associations with positive connotations for in-ideology—for example, justice (left) and patriotism (right)—and negative connotations for out-ideology—for example, racism (right) and socialism (left). The model’s applicability is demonstrated in scaling parliamentary speeches and is reliable across different model specifications in terms of construct and external validity. The study advances the understanding of ideological associations and their role in political research by highlighting the importance of distinguishing between in- and out-ideology in explaining ideological language across the political spectrum.